Osteoblastoma of the Os Capitatum - Çağrı Kaptan; Halil Atmaca (Case Reports in Orthopedics)
An osteoblastoma is a primary benign bone tumor, which is rarely seen in hand bones. Osteoblastoma is generally seen in spine, pelvis, and long bones. However, there are a few case reports of osteoblastoma in wrist and hand bones. To our knowledge, up to now, only one male patient with osteoblastoma in capitate bone was reported. We report the first female case of osteoblastoma of capitate bone and discuss diagnosis and treatment.